THE CONSTRUCTION OF LANGUAGE HUMOR TOWARDS INDONESIAN LANGUAGE CULTURE - Rawuh Yuda Yuwana; Desca Angelianawati; Aldianus Tuwar; Cintya Putri Manik (PT Akselerasi Karya Mandiri, 2023)
This research explores the intricate interplay of humour, psycholinguistics, morphology, themes, rheme, and language intelligence within the Indonesian language context. Through thorough analysis, the study breaks down humorous linguistic constructs, emphasizing the significance of abrupt contextual shifts and linguistic disruptions as the essence of Indonesian humour. By examining themes and rheme, the research reveals how humour arises from unexpected linguistic contrasts, challenging reader expectations. From a psycholinguistic perspective, the study dissects the cognitive processes that underlie humour comprehension, shedding light on the crucial role of language intelligence in recognizing and appreciating linguistic nuances. The research methodology involved extensive text analysis, delving into various linguistic elements and their impact on humour. The study concludes that language structure, psycholinguistics, and the manipulation of themes and rheme are fundamental aspects of Indonesian humour, underscoring the linguistic complexity inherent in comedic expression.